Ethyl -butyl ether synthesis using carbon catalysts from lignocellulose - Alexander M Puziy; Yuriy N Kochkin; Olga I Poddubnaya; Mykola M Tsyba (Adsorption Science & Technology)
Porous structure, surface chemistry and catalytic properties of carbon catalysts with various acid groups in ethyl tert -butyl ether synthesis were studied. Carbon catalysts were obtained by phosphoric acid activation followed by sulphonation of lignocellulosic feedstocks of different origin. Porous structure of carbon catalysts was characterized by nitrogen adsorption. Surface chemistry was investigated by potentiometric titration. Carbon catalysts obtained from lignosulphonate and sucrose showed the highest catalytic activity in ethyl tert-butyl ether synthesis (reaction rate at 120℃ is 4.3–5.2 × 10 −6  mol·g −1 ·s −1 ), is comparable to activity of Amberlyst-15 (5.0 ×10 −6  mol·g −1 ·s −1 ). Calculated turnover frequency (TOF) of sulphonic groups (pK a  = −2.5) equals 0.00116 s −1 , polyphosphate groups (pK a  = 1.9) 0.01019 s −1 , strong carboxylic (pK a  = 3.6) 0.00202 s −1 and 0 s −1 for weak carboxylic (pK a  = 6) groups. The activity of acid groups with pK a lower than 3.6 is higher than the activity of sulphonic groups of Amberlyst-15 (TOF 0.00115 s −1 ).